A20 negatively regulates necroptosis-induced microglia/macrophages polarization and mediates cerebral ischemic tolerance via inhibiting the ubiquitination of RIP3 - Meiqian Qiu; Wenhao Zhang; Jiahua Dai; Weiwen Sun; Meijing Lai; Shiyi Tang; En Xu; Yuping Ning; Lixuan Zhan (Cell Death and Disease)
Abstract Neuronal necroptosis appears to be suppressed by the deubiquitinating enzyme A20 and is capable to regulate the polarization of microglia/macrophages after cerebral ischemia. We have demonstrated that hypoxic preconditioning (HPC) can alleviate receptor interacting protein 3 (RIP3)-induced necroptosis in CA1 after transient global cerebral ischemia (tGCI). However, it is still unclear whether HPC serves to regulate the phenotypic polarization of microglia/macrophages after cerebral ischemia by mitigating neuronal necroptosis. We hence aim to elucidate the underlying mechanism(s) by which the ubiquitination of RIP3-dependent necroptosis regulated by A20 affects microglia/macrophages phenotype after cerebral ischemic tolerance. We found that microglia/macrophages in CA1 of rats underwent M1 and M2 phenotypic polarization in response to tGCI. Notably, the treatment with HPC, as well as inhibitors of necroptosis, including Nec-1 and mixed lineage kinase domain-like (MLKL) siRNA, attenuated neuroinflammation associated with M1 polarization of microglia/macrophages induced by tGCI. Mechanistically, HPC was revealed to upregulate A20 and in turn enhance the interaction between A20 and RIP3, thereby reducing K63-linked polyubiquitination of RIP3 in CA1 after tGCI. Consequently, RIP3-dependent necroptosis and the M1 polarization of microglia/macrophages were blocked either by HPC or via overexpression of A20 in neurons, which ultimately mitigated cerebral injury in CA1 after tGCI. These data support that A20 serves as a crucial mediator of microglia/macrophages polarization by suppressing neuronal necroptosis in a RIP3 ubiquitination-dependent manner after tGCI. Also, a novel mechanism by which HPC functions in cerebral ischemic tolerance is elucidated.